Motives on youtube usage among undergraduate students for self-satisfaction / Intan Zahrah Mat Hussin - Mat Hussin, Intan Zahrah (Universiti Teknologi MARA, 2022)
Social media usage is an emerging trend among students in Malaysia. YouTube, a social medium that is the current Web 2.0 tool, has played a significant part in assisting students' everyday life. This study aims to assess students' level of motives in using YouTube for self-satisfaction. Specifically, this study wants to determine the relationship between social interaction motive, entertainment motive, and information-seeking motive with self-satisfaction in using YouTube besides to find out the best predictor for self-satisfaction on YouTube usage. It is assumed that there is a positive association between social interaction motive, entertainment motive, and information-seeking motive with self-satisfaction respectively. The quantitative research design using the survey method was chosen for this study by distributing online survey questionnaires to Bachelor's Degree students in UniSZA Gong Badak Campus, Malaysia. Probability stratified random sampling has been selected for sample selection. Among 129 participants in this study, most of them are female coming from the 21-23 age group. The relationships between the variables are significant where there is a high level of entertainment motive and information-seeking motive whereas social interaction motive is low among undergraduate students. Results showed students' motives in using YouTube is mostly for entertainment, followed by information-seeking and social interaction motives. The best predictor for self-satisfaction on YouTube usage is entertainment motive among university students. These findings suggest that YouTube can self-satisfy undergraduate students with the motives of entertainment, information seeking and social interaction. This study sheds light on the dimensions of using YouTube for entertainment with the incorporation of education for the students to gain knowledge either in the general or academic context.